Eficiência bioeconômica da suplementação de novilhos em pastagens de Capim Marandu - De Carvalho, Daniel Marino Guedes; Da Silva Cabral, Luciano; Zervoudakis, Joanis Tilemahos; De Moraes, Eduardo Henrique Bevitori Kling; Benatti, João Marcos Beltrame [UNESP]; Koscheck, Jefferson Fabiano Werner; De Oliveira, André Alves (My University, 2014)
The objective was to evaluate the effect of mineral salt (MS), multiple (MS), energy (ES) and protein supplements (PS) on performance, behavior and production cost of the cattle in Marandu grass pasture. The experiment lasted 84 days, conducted in the experimental area consists of four paddocks of 1.45 ha. Twenty steers were used with age and initial body weight of 172 kg and 10 months, respectively. It used a completely randomized design with four treatments and five replicate. The energy, multiple and protein supplements was supplied on 1.0 kg day-1. The animals were weighed at the beginning and end of the experiment, to determine the average daily gain (ADG). The weight gain of animals was 0.380, 0.600, 0.750 and 0.730 kg/day, respectively, for treatments MS, ES, MS and PS, have been verified statistical difference between supplemented animals and animals than received only mineral salt. The multiple supplement produced ADG 49.33% and 20.00% higher than the mineral salt. The multiple and protein supplements permitted average performance 18.92% higher than the energy supplement. There was no difference in behavior of grazing (P> 0.05). Animals receiving the mineral mixture had time to 8.40 hours of grazing animal day-1. The multiple supplement provided better economic performance considering the sale of animals to 350 kg body weight.
Bio-economic efficiency of supplementation for steers in Marandu Grass pasture
Keywords: Behavior; Energy; Performance; Production cost; Protein; Supplements